RNA Analysis and Clinical Characterization of a Novel Splice Variant in the NSD1 Gene Causing Familial Sotos Syndrome - Villate, Olatz; Maortua, Hiart; Tejada, María-Isabel; Llano-Rivas, Isabel (Frontiers in Pediatrics, 2022)
Background: Sotos syndrome is an autosomal dominant disorder characterized by overgrowth, macrocephaly, distinctive facial features and learning disabilities. Haploinsufficiency of the nuclear receptor SET domain-containing protein 1 (NSD1) gene located on chromosome 5q35 is the major cause of the syndrome. This syndrome shares characteristics with other overgrowth syndromes, which can complicate the differential diagnosis Methods: Genomic DNA was extracted from peripheral blood samples of members of the same family and targeted exome analysis was performed. In silico study of the variant found by next-generation sequencing was used to predict disruption/creation of splice sites and the identification of potential cryptic splice sites. RNA was extracted from peripheral blood samples of patients and functional analyses were performed to confirm the pathogenicity. Results: We found a novel c.6463+5G>A heterozygous NSD1 gene pathogenic variant in a son and his father. Molecular analyses revealed that part of the intron 22 of NSD1 is retained due to the destruction of the splicing donor site, causing the appearance of a premature stop codon in the NSD1 protein. Conclusions: Our findings underline the importance of performing RNA functional assays in order to determine the clinical significance of intronic variants, and contribute to the genetic counseling and clinical management of patients and their relatives. Our work also highlights the relevance of using in silico prediction tools to detect a potential alteration in the splicing process.